Real-life effectiveness and safety of dupilumab in adult patients with moderate-to-severe atopic dermatitis - SALMAN, ANDAÇ (WILEY, 2022)
Atopic dermatitis (AD) is a common, chronic inflammatory condition with a substantial negative impact on the quality of life. Dupilumab, the first biologic approved for the treatment of moderate-to-severe AD, binds IL-4R alpha and inhibits signaling of both IL-4 and IL-13. This study aimed to determine the real-life effectiveness and safety of dupilumab treatment in patients with moderate-to-severe AD. The results of the study indicates high effectiveness and safety of dupilumab in real-life conditions. The treatment was continued during the COVID-19 pandemic in most of the patients without any adverse outcome. The rate of conjunctivitis was higher compared to clinical trials, nevertheless treatment was not discontinued in any patients due to adverse effects.
Keywords: atopic dermatitis; dupilumab; real-life; ADVERSE EVENTS; EFFICACY